Ideology and power in Norway and Iceland, 1150-1250 - Coroban, Costel (Cambridge Scholars Publishing, 2018)
"This book provides an analysis of the ideology of power in Norway and Iceland as reflected in sources written during the period 1150-1250. The main focus is explaining the way that Kings' power in Norway, and that of chieftains in Iceland, was idealised in important texts from the 12th and 13th centuries (Sverris saga, Konungs skuggsjá, Hákonar saga Hákonarsonar, Íslendingabók, Egils saga, Laxdæla saga and Þórðar saga kakala). The originality of this work consists in the fact that it is the first monograph to comparatively analyse the ideology of power in Iceland, looking specifically at representations of king(s) and chieftains during the Civil Wars period, and compare the findings to those pertaining to Norway."--